The relationship between social media use and critical thinking ability on critical reading skills among university students - Dinda Amelia; Maman Suryaman; Sudiati Sudiati (Jurnal Penelitian Ilmu Pendidikan, 2024)
In the digital era, social media serves not only as a medium for communication and entertainment but also as a potential tool for developing academic competencies such as critical reading. This study aims to examine the relationship between social media use and critical thinking ability in relation to university students’ critical reading skills in Yogyakarta. Employing a quantitative method with a correlational approach, the research involved a sample of 40 students selected through stratified random sampling. Data were gathered using questionnaires, critical thinking tests, and critical reading assessments, all validated through Cronbach’s Alpha. The findings revealed a significant correlation among social media use, critical thinking ability, and critical reading skills. Regression analysis indicated that critical thinking ability had a significant effect on critical reading skills, whereas the influence of social media use was less pronounced. However, simultaneous analysis demonstrated that social media use and critical thinking ability together contributed to the improvement of critical reading skills. These results highlight the dual role of social media as both a facilitator and a distraction in academic contexts. Educators are therefore encouraged to incorporate media literacy and critical thinking training to optimize the positive impact of social media on students’ learning processes.